SAPATHA DALAM RELASI KUASA DAN PENDISIPLINAN PADA MASYARAKAT BALI KUNO ABAD IX-XIV MASEHI - I Wayan Ardika; I Ketut Setiawan; IGN Tara Wiguna; I Wayan Srijaya (Berkala Arkeologi, 2018)
Inscription is a written record which contains regulation or law and should be obeyed by officers or functionaries and community in general. Sapatha or curse was normally written at the end of the inscription which states the punishment for those who objected the regulations or laws. People punished morally if they objected the regulations or law include seven times to be reincarnated and surfering in all their lives. Sapatha or curse was seen as a discourse in relation of power and knowledge of the kings who reigned in the Old Balinese period. This article explores the sapatha or curse in Old Balinese inscriptions dated from the IX up to XIV century. The aim of this article is to describe the relationship of power and knowledge, as well as discipline and punishment in ancient Bali. Data was gained through documentary studies and interpreted hermeneutically. Theories of ideology, knowledge and power, as well as discipline and punishment will be applied in this article.